Knowledge and Behavior of TB Patients Recovered and Not Recovered at the Kambaniru Community Health Center of East Sumba Regency - NYOKO, YUNETI OCTAVIANUS; AMA, YULIUS TAMO (Poltekkes Kemenkes Kupang, 2017)
Introduction: Pulmonary TB is one of the most contagious diseases in East Sumba. According to data obtained from the Health Office of East Sumba Regency in 2016, there are 232 people with TB BTA (+). The knowledge and behavior of Pulmonary TB sufferer are very influential to cure the disease. Methods: This research uses a descriptive method. Sampling technique in total sampling. Results: The result of the research was 47 respondents (46.8%), who were known as much as 8 respondents (17%), well knowledge of 17 respondents (36.2%). The behavior of respondents showed that the behavior was less than 19 respondents (40.4%), who had enough behavior as many as 10 respondents (21.3%) and good behavior as many as 18 respondents (38.3%). Conclusion: Of the 47 respondents most aged 40-59 years (34%), female (26,3%), elementary school (23,3%) and employed 44 people (93.6%), as many as 22 people (46.8%), behaved less as many as 21 people (44.6%).